MODEL OF ORGANIZATIONAL AND INFORMATION SUPPORT OF SMART CITY STRATEGY DEVELOPMENT IN THE CONDITIONS OF DIGITAL ECONOMY - Momot, Tetiana; Muraev, Yevgen (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2021)
The article is devoted to the study of the theoretical and methodological foundations of the development of a model of organizational and information support for the development of smart city strategy in a digital economy. The subject of the study is a set of theoretical, methodological and practical aspects to ensure the formation of a model of organizational and information support for the development of a strategy for smart cities in a digital economy. The purpose of the article is to develop theoretical and methodological provisions and substantiate practical recommendations for the formation of a model of organizational and information support for the development of a strategy for smart cities on a balanced scorecard in a digital economy.: to analyze the most progressive cities in the world to create and implement a strategy of smart cities in terms of leading international rankings of smart cities; to study and systematize methodical approaches to the assessment of smart cities according Objectives to international rankings in the digital economy; summarize the advantages and disadvantages of ranking smart cities; to offer a model of organizational and information support for the development of a strategy for smart cities on a balanced system of indicators in a digital economy. In the course of the research the following methods were used: abstract-logical analysis, theoretical generalization and systematization, system analysis. The paper analyzes the most progressive cities in the world in terms of leading international rankings of smart cities in the digital economy. Methodological approaches to the assessment of smart cities according to international rankings in the digital economy are summarized; their advantages and disadvantages are identified. It is proved that today there is no single methodological approach to assessing the rating of a smart city. A model of organizational and information support for the development of a strategy for smart cities on a balanced scorecard in a digital economy has been developed. Conclusions. A comparative analysis of the Top 10 smartest cities in the world in terms of leading international rankings; on the basis of the conducted analysis the components of the assessment of smart cities are systematized within the framework of the studied methodological approaches to the assessment of smart cities according to international rankings. a model of organizational and information support for the development of a smart cities strategy on a balanced system of indicators was developed, which is considered as an integrated assessment system; the information and analytical tools for assessing the level of balanced development of smart cities, is an informative basis for positioning the city on the selected components of a balanced scorecard are proposed.